Albumin glycation in Alzheimer's disease patients: Results from the AMBAR trial: Molecular and cell biology/protein‐protein interactions. (7th December 2020) - Ortiz, Ana Maria; Minguet, Carla; Mestre, Anna; Orellana, Adelina; Núñez, Laura; Boada, Mercè; Ruiz, Agustín; Páez, Antonio; Costa, Montserrat
Abstract: Background: A novel therapeutic approach that includes therapeutic plasma exchange (TPE) plus albumin replacement has shown to slow cognitive and functional decline in mild‐to‐moderate Alzheimer's disease (AD) patients (AMBAR Trial, NCT01561053). We previously described higher levels of early glycated albumin (eGA) in baseline AD plasma samples from a Phase II clinical trial using TPE with albumin replacement (EudraCT#2007‐000414‐36), compared to age‐matched healthy controls. Moreover, treatment showed a positive but transient effect in lowering eGA. Glycated albumin is known to have impaired binding capacity and to be less effective in preventing amyloid beta peptide aggregation (Ramos‐Fernández et al, 2014.JAD;643). In the present study, eGA in samples from AMBAR trial has been evaluated to confirm previous findings. Method: We measured eGA in AMBAR baseline serum samples (n=318) from mild‐moderate AD patients (MMSE:16‐26) and compared with serum samples from age‐matched healthy controls (HC) (n=25, MMSE:28‐30). Samples collected throughout the two intervention regimens in AMBAR were also analyzed: conventional TPE period for 6 weeks (processing 1 plasma volume [2500‐3000mL]; 1TPE/week); and low volume plasma exchange [LVPE] period for 12 moths (removing approximately 1/3 plasma volume [similar to a plasma donation]; 1LVPE/month) in comparison to non‐treated AD controls. QuantiLab Glycated Albumin assay (Werfen) on Beckman‐Coulter AU5800 was used. Values are expressed as %eGA, median‐IQR. Result: Results of eGA in AMBAR baseline samples was similar to those from HC (13.0% [12.2%‐14.0%] vs 12.6% [12.1%‐13.8%], respectively). Of note, percentage of patients with eGA above the normal reference range (9%‐16%) in AMBAR AD patients was higher than in HC (10% vs 0%). A transient effect in lowering eGA after each intervention period in AMBAR was observed: change from baseline eGA after conventional TPE and after LVPE periods were ‐4.2% (‐5.3% to ‐2.8%) and ‐1.2% (‐1.8% to ‐0.5%) respectively. Interestingly, when considering only patients with hyperglycated albumin baseline levels (eGA≥16%; n=29), all patients except one reached the normal reference range after the first TPE intervention (11.2% [10.5%‐13.0%]). Conclusion: PE with albumin replacement, in particular conventional TPE regime, caused a transient but noticeable effect in lowering eGA levels in AD patients, which allowed patients with hyperglycated albumin to reach normal reference values.